Biogas Productivity Using Cow Feces Input and Palm Oil Empty Affluent Soaking Water - F.Ramadhani; N. Ginting; J.A. Lase (Talenta Publisher, 2023)
Soaking water of empty palm oil fruit bunches is a waste that is usually disposed of in straw mushroom cultivation. It turns out that this soaking water still contains nutrients, so it is suitable as input for biogas along with cow faeces. Therefore a study was carried out while the treatments used were P0 (cow faeces + empty palm oil bunches soaking water) and P1 (cow faeces + empty palm oil bunches soaking water + 5% bioactivator). All biogas input was fermented for 28 days, and the fermentation parameters were gas pH, gas pressure, gas volume, flame test and colour. The results showed that adding 5% bio activator significantly affected the gas produced. Maximum production in both treatments occurred on day 28, i.e. cow feces + empty palm oil bunches soaking water with a pH of 7.61, resulting in a gas pressure of 416.925 pa and a gas volume of 20 L. Meanwhile,Â cow faeces + empty palm oil bunches soaking water + 5% bioactivator cause a pH of 7.91, produces a gas pressure of 588.6 pa and a gas volume of 30 L.